2021
DOI: 10.47067/ramss.v4i1.108
|View full text |Cite
|
Sign up to set email alerts
|

A Step towards enhancement of Macroeconomic Performance of Pakistan: Do Oil Price, Public Expenditures and Financial Development Matter?

Abstract: Oil price fluctuations have vital importance in macroeconomic performance. Our study demonstrates the impact of oil price fluctuations on the trade balance and economic growth in Pakistan. We employ a linear autoregressive distributed lag model (ARDL) for the period 1970-2018. The results showed that oil price negatively affected the total trade balance in Pakistan other control variables like the real effective exchange rate, real GDP (Home country) and financial development also negatively affected. While re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…The findings in Table 6 indicate that oil prices have a larger effect on exports for importing countries when its level surpasses the optimal threshold level, confirming the results of Chaudhry et al (2021) which showed that an increase in the price of oil is not in favor of the trade balance of oil-importing countries. Soaring oil prices tend to deteriorate the trade balance and the economic growth of these countries.…”
Section: The Regression Results Displayed In Tablesupporting
confidence: 75%
See 1 more Smart Citation
“…The findings in Table 6 indicate that oil prices have a larger effect on exports for importing countries when its level surpasses the optimal threshold level, confirming the results of Chaudhry et al (2021) which showed that an increase in the price of oil is not in favor of the trade balance of oil-importing countries. Soaring oil prices tend to deteriorate the trade balance and the economic growth of these countries.…”
Section: The Regression Results Displayed In Tablesupporting
confidence: 75%
“…Soaring oil prices tend to deteriorate the trade balance and the economic growth of these countries. According to Chaudhry and al. (2021) findings, lower oil prices improve the trade balance as well as economic growth.…”
Section: The Regression Results Displayed In Tablementioning
confidence: 99%
“…This methodology has advantages over traditional econometric methodologies. It can be applied even in the case of a small sample; It is suitable if all variable is stationary at level I(0) or 1st difference or mix the order of integration (Chaudhry et al, 2021;Farooq et al, 2020). The study has applied the F-bound test to check the long-term co-integration between variables.…”
Section: Econometric Strategymentioning
confidence: 99%
“…The growing dependance on imported fuels in total energy consumption has significantly exposed the internal and external accounts of the country to the movement of global fuel prices, inter-alia, crude oil, coal and re-gasified liquified natural gas (RLNG). Accordingly, the unfavorable movements cause deterioration of the trade balance, real effective exchange rate, and overall financial development (Chaudhry et al 2021). This can be demonstrated through the trend of the progressive exposure of: (i) percentage energy subsidies in the total fiscal budget; (ii) energy imports (Bln.…”
Section: Introductionmentioning
confidence: 99%